Assessment of Potentially Inappropriate Medications and Prescription Appropriateness in Geriatics at Teritiary Care Hospital: A Prospective Observational Study - Wazir, Wahiba Mohammed; Afreen, Saba; IFFATH, FARIA; Rafia, Amtul Muqeet; Ur Rahman, Mohammed Ateeq (Journal of Drug Delivery and Therapeutics, 2020)
Background: Elder people are a diversified group commonly presenting with multiple comorbid illnesses resulting into multiple prescriptions which in turn increases adverse effects and polypharmacy. Potentially inappropriate medications (PIM) further contribute to this risk. Therefore, the aim of this study was to assess the prescription appropriateness and (PIM) in geriatrics as per WHO core prescribing indicators and Beer’s Criteria, 2015 respectively. Methods: A prospective observational study was conducted in Osmania General Hospital, a Tertiary Care Teaching Hospital from December 2018 to May 2019. A total of 100 case records of inpatients greater than or equal to 60 years of age, in general medicine wards were reviewed. Relevant information was recorded in a structured proforma and data was evaluated. Results: Out of 100 patients, 70 patients were male and 30 patients were female. Majority of them were from the age group of 65-70 years. There were 34% patients prescribed at least one PIM. Polypharmacy was observed in all patients. Average no. of drugs per prescription was 10.5%.Percentage of drugs prescribed from EDL (Essential drug list) were 84%.The p value of WHO core prescribing indicators was assessed using chi square test and was found to be significant. Conclusion: Our study found WHO core prescribing indicators to be deviated from the optimum values set by WHO and high prevalence of Potentially Inappropriate Medications as per Beers criteria 2015. This highlights the need of future research work, strategies and regulatory measures focusing on geriatric patients and also encouraging prescribers to use the WHO core prescribing indicators and Beers criteria while prescribing elderly for providing optimum healthcare. Keywords: Beer’s criteria, Geriatrics, WHO prescribing indicators, Polypharmacy. Ageing, Potentially Inappropriate Medications.